Characteristics and sedimentological significance of acoustic anomalies in silty seabed in the Yellow River subaqueous delta. (1st October 2022) - Wang, Fangqi; Song, Yupeng; Liu, Senbo; Tao, Changfei; Lin, Xubo
Abstract: Due to extraordinary natural geographical features, seabed topography, and sediment sources, wave-induced silt liquefaction is a common occurrence in the subaqueous delta of the Yellow River, China. When liquefaction occurs, the original sedimentary structure of silt is destroyed; after liquefaction, the sediment particles are rearranged and reconsolidated, resulting in distinct physical and mechanical differences between the liquefied material and the nearby adjacent strata that have not been subjected to liquefaction. Based on data from geotechnical testing (GT), scanning electron microscope (SEM) images, and sub-bottom profiling (SBP), the physical and acoustical characteristics of silt remoulded by wave-induced liquefaction (SRL) in the Yellow River subaqueous delta are determined. According to the GT results, liquefaction resulted in distinct decreases in the water content (2.6%), the void ratio (0.056), and the clay content (4.52%), as well as slight increases in the wet density (0.01 g/cm 3 ), the dry density (0.05 g/cm 3 ), and the grain size ( d 50 ) (0.015 mm). Per our SEM analyses, the SRL material is denser than the unremoulded silt, attributed to the rearrangement and reconsolidation of the silt particles. As can be determined from the high-resolution SBP data, that acoustically, the SRL is distinctly different from the adjacent intact strata. The smooth funnel-shaped features demarcate the extent of the region that has been subjected to a specific liquefaction and silt reconsolidation event. Due to the presence of a fault-like uplifted reflection event in the underlying strata, the SRL produces positive sound velocity anomalies on the order of 53–127 m/s. Analyses of the physical and acoustical characteristics of the SRL provides valuable insight into the engineering properties of seabed silt. Highlights: Focusing on physical and acoustic properties of silt after being remoulded by wave-induced liquefaction. Both the physical features from borehole and SEM images and the acoustical features from high-resolution SBP prove that the liquefaction and remoulding process significantly improves the engineering properties of the seabed silt. The positive sound velocity anomalies are estimated to have magnitude of 53–127 m/s.